Is New Zealand prepared to deal with arboviral diseases? - José G. B. Derraik; Charles H. Calisher (Elsevier, 2004)
Abstract To now, New Zealand has been spared arboviral diseases, except for the odd imported infection. However, two exotic vector mosquitoes (Ochlerotatus camptorhynchus and Ochlerotatus notoscriptus) have become established in New Zealand and the routine arrival of infected people from overseas may soon lead to local arboviral transmission. Large populations of wild wallabies and Brushtail possums could serve as reservoirs of Ross River virus and other arboviruses. Several other exotic mosquito species, including important disease vectors such as Aedes albopictus and Aedes aegypti, have already been intercepted in New Zealand. It is clear that increased border surveillance is necessary if we are to interdict the establishment of such species. We recommend several measures that should be adopted, including increased training and awareness of public health officials, clinicians and the general public, and taking appropriate steps to make New Zealand self‐sustainable in terms of arboviral surveillance, diagnosis, and prevention.